Urgent Prioritization of Conservation Sites for the Jagüilla (Tayassu pecari) in the Honduran Moskitia Region - Portillo Reyes, Hector Orlando; Martínez, Marcio (THERYA, 2024)
Tayassu pecari (known in Honduras as jagüilla and Wari in Miskito), is one of two types of wild pigs (chanchos de monte) found in Honduras (Marineros and Martinez 1998). Currently, its conservation status on the IUCN red list is vulnerable (VU) and critically endangered (CR) for Honduras (WCS 2021). According to Portillo and Elvir (2016), the potential area for jagüilla distribution is 6,126 km2 corresponding to 5.5 % of the country territory. The potential area for this species is in three sites, mainly protected area of the Reserva del Hombre and the Biósfera del Río Plátano (RHBRP), with approximately 70 % of the predicted potential distribution (4,288 km2), 20 % (1,225 km2) in the indigenous territories of Rus Rus, Mocorón and Warunta, and 10 % (613 km2) in the Tawahka Asagni Biosphere Reserve. The aim of this note is to contribute to the prioritization of four sites where evidence of small groups of jagüillas have been found: 1) Sierra de Agalta National Park. 2) the core zone of the RHBRP. 3) the cultural zone of the RHBRP. 4) the Warunta Mountains. Records of jagüilla were obtained from diverse sources (Table 1), mainly from biological monitoring implemented in various locations of the Río Plátano Biosphere (buffer zone, cultural zone, and core zone), Warunta Mountains, riparian forest in Rus Rus River, as well as the Tawahka Biosphere Reserve through the use of camera traps which were carried out between 2016 and 2022. In the RHBRP jagüilla were registered in two of the three zones these being the core zone and the cultural zone; no records of the species were obtained in the buffer zone. In these localities, groups of 2 to 45 individuals were documented. For the Warunta region in the Indigenous Federation of Mocoron and Segovia Zone (FINZMOS territory), tracks, and photographic evidence of a large group of 50 to 100 individuals were registered moving in this territory covered mainly by primary broadleaf forest. Hunting by invasive settlers and habitat loss due to deforestation in protected areas, has had an impact on jagüilla populations, reducing this species in the Honduran Moskitia region as mentioned by Portillo and Elvir (2016). One of the important aspects of this work is to highlight the findings in NP Sierra de Agalta as a potential site for future research and biological monitoring efforts for the development of conservation processes for the jagüilla as a park conservation target (Figure 2) since the last records of this species were documented at La Quebrada del Sol, NP Sierra de Agalta, in 1994 (Marineros and Martínez 1998). It is of utmost importance to establish monitoring and participatory conservation processes with the local communities (Larsen 2019; Martínez et al. 2022).